Controlling dynamic magnetic properties of coordination clusters via switchable electronic configuration. (13th April 2021) - Huang, Wei; Ma, Xiao; Sato, Osamu; Wu, Dayu
Abstract : Large-sized coordination clusters possess unique dynamic properties for potential applications. This review summarizes the recent progress in coordination clusters with dynamic magnetic properties via stimuli-responsive electronic configuration. Abstract : Large-sized coordination clusters have emerged as a new class of molecular materials in which many metal atoms and organic ligands are integrated to synergize their properties. As dynamic magnetic materials, such a combination of multiple components functioning as responsive units has many advantages over monometallic systems due to the synergy between constituent components. Understanding the nature of dynamic magnetism at an atomic level is crucial for realizing the desired properties, designing responsive molecular nanomagnets, and ultimately unlocking the full potential of these nanomagnets for practical applications. Therefore, this review article highlights the recent development of large-sized coordination clusters with dynamic magnetic properties. These dynamic properties can be associated with spin transition, electron transfer, and valence fluctuation through their switchable electronic configurations. Subsequently, the article also highlights specialized characterization techniques with different timescales for supporting switching mechanisms, chemistry, and properties. Afterward, we present an overview of coordination clusters (such as cyanide-bridged and non-cyanide assemblies) with dynamic magnetic properties, namely, spin transition and electron transfer in magnetically bistable systems and mixed-valence complexes. In particular, the response mechanisms of coordination clusters are highlighted using representative examples with similar transition principles to gain insights into spin state and mixed-valence chemistry. In conclusion, we present possible solutions to challenges related to dynamic magnetic clusters and potential opportunities for a wide range of intelligent next-generation devices.